Directors’ influence on pay-based performance - Sherliza Puat Nelson,; Salsabila Abd Rahim, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The objective of this study is to examine earnings management influence on directors’ remuneration. Taking a calculation of the empirical evidence of earnings management, firm performance and directors’ remuneration, this study is able to demonstrate that pay-performance is not influenced by earnings management. Data for this study were extracted from the annual reports of 678 non-financial public listed companies in Malaysia for the years of 2009, 2010 and 2011 giving rise to final 2021 observations. The findings highlighted that earnings management played no role in determining the directors’ remuneration. However, the findings documented a significant and positive association between the directors’ influence and the directors’ remuneration. This study contributes to the growing literature by providing evidence which demonstrate that pay-performance was not directly influenced by earnings management but by the influence of the executive directors. More importantly the study documents even under strong governance, Malaysian listed firms are influenced by the executive directors.